Fresno Superior Court Special En Banc In Memoriam Session in Jury Assembly Room - Watkins, Howard::::::::: (1987)
Speakers Robert Wash, Robert Sears, Presiding Judge Stephen Henry, Marion Mosely, Charles Barrett, Jr. and Lawrence